If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3p + -16 = p + 4 Reorder the terms: -16 + 3p = p + 4 Reorder the terms: -16 + 3p = 4 + p Solving -16 + 3p = 4 + p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. -16 + 3p + -1p = 4 + p + -1p Combine like terms: 3p + -1p = 2p -16 + 2p = 4 + p + -1p Combine like terms: p + -1p = 0 -16 + 2p = 4 + 0 -16 + 2p = 4 Add '16' to each side of the equation. -16 + 16 + 2p = 4 + 16 Combine like terms: -16 + 16 = 0 0 + 2p = 4 + 16 2p = 4 + 16 Combine like terms: 4 + 16 = 20 2p = 20 Divide each side by '2'. p = 10 Simplifying p = 10
| 42-4*3+9/3 | | 4(y+2)=36 | | 4500=3000(1+0.08*t) | | 42-5*4+6/2 | | 1/2+0.5 | | 12r+4r+(4-6/4r) | | 6a+5/6a=12-4/3 | | x^4+5x^3-20x-16=0 | | 25x=100+50 | | y-7/3=7y+13 | | X^2+18X=40 | | h=-4.9t^2+19.6t-9.6 | | 3.2*10-.5x=17.7x*10 | | 600x+5000=170 | | 3x-7=5x+3(x-4) | | 2(3-2x)+6=6x | | 5/x+6/5x^2 | | 8x-3x=105 | | 2.4x-2.2=4.4-3.6x | | g(x)=(x+20)x^2 | | -6(x+10)=24 | | 4(3x)=12 | | 7=42/3x | | 1/x=2/10 | | x^2-1200x-3025=0 | | 2(2x-7)=28 | | 4x-1/2=7 | | 2(2x-7)=12 | | 3x/7+8=11 | | 5x+21=2x+6 | | 2a-3/10a | | -2/5a+a/5 |